Analisis Kemampuan Berpikir Kritis dan Penalaran pada Soal Open Ended: Dampak Model Problem Based Learning dan Model Discovery Learning - Mujahidah, Mujahidah; Nursalam, Nursalam; Suharti, Suharti; Majid, Ahmad Farham; Angriani, Andi Dian (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2025)
Critical thinking and reasoning skills are essential cognitive aspects that must be developed in mathematics education to address the demands of the 21st century. This study aimed to analyze the differences in students’ critical thinking and reasoning abilities in solving open-ended problems through the implementation of Problem-Based Learning and Discovery Learning models. A quantitative approach was used, employing an experimental method with a factorial design. The sample consisted of two groups of students, each receiving a different treatment, with a total of 58 participants. The research instrument was a set of open-ended essay questions. Data were analyzed using univariate t-tests and multivariate mean difference tests. The findings indicated no significant difference in critical thinking skills between students taught with the two learning models. However, a significant difference was found in reasoning ability, as well as a simultaneous difference in both critical thinking and reasoning between the groups.